Iqbal’s Concept of Love - Muhammad Anwar Aneeq; Shabbir Ahmad Qadri (دریافت)
Iqbal considers love as the basis of life. The wonderful manifestation of universe is driven by love. Iqbal's fundamental philosophy is selfhood.  Life cannot sustain it- self without love. Love is the basic passion of a man's life. It is the enhanced form of affection. There is elegance and exhilaration in the realm of water and earth due to love. The power of conquest owes to love. Love, the force that is free from the limits of time and space. Cannot be guaged with the measuring stick of day and night. In a nutshell love is the key to the whole universe. Love is the ecstasy of life and under it is covered man's glory. The foundation stone of every magnum opus is laid on love. Love is the essence of life. Love brings vitality to life and makes one understand the way of life